THE CREATION OF AN ELECTRONIC DATABASE FOR STUDYING FOSSIL FLORAS OF NORTHERN CAUCASIA - Ruban D.A. (My University, 2003)
Data on the Paleozoic and Mesozoic fossil plants of Northern Caucasia have been collected and integrated by the author on the basis of an electronic database. The structure of this database is aimed at the effective representation of information; i.e., specific data can be retrieved as requested by the end user. The available material provides fairly complete data on the generic composition of the floristic assemblages that existed in this region.